Natural valuable compound extraction from onion by-products using a pulsed electric field (International Journal of Biology and Chemistry, 2019)
Onion by-products, a waste generated from fruit processing industry, is a potential source of phenolic compounds that are known for their anti-oxidative properties. The influence of pulsed electric field(PEF) treatment on the bioactive compounds from onion by-products at different pulse voltage (PV); 2000,4000, 6000Vand number of pulse (NP); 40, 50, 60 has been investigated. Response surface methodology,based on a Face-Centered Experimental Design (FCED) was used to determine optimal PEF treatment andoptimize extraction yield, antioxidant strength, total phenolic compound (TPC),and quercetin content. Theexperimental data were fitted to a second‐order polynomial equation and also profiled into the corresponding 3‐D contour plots. Optimal extraction conditions were as follows:PV were 4102.97 V and and NP 51.43. Under these conditions, TPC, DPPH, FRAP,Quercetin and extraction yield were 48.912 ± 6 mg/kg, 50.366 ± 1 %, 465.414 ± 5 μmFe2/l, 31.761 ± 0.5 mg/100g and 88.107 ± 1% ; respectively and matching well with the predicted value. The results demonstrated that PEF could be a very effective method for continuousextraction of natural compounds.